2018
DOI: 10.1186/s12903-018-0543-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of denture surface roughness and host factors on dental calculi formation on dentures: a cross-sectional study

Abstract: BackgroundDental calculi formation on dentures can worsen the oral cavity environment by complicating oral hygiene. However, few studies have investigated the effect of how patients use and manage their dentures, denture surface roughness, and host factors such as oral cavity dryness and saliva properties on denture cleanliness and denture dental calculi formation. Accordingly, we conducted the present survey to evaluate these factors to clarify the strength of the influence of each factor.MethodsWe enrolled 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Many studies concluded that toothbrushing significantly increases surface roughness [ 24 , 27 ] and any surface roughness above a threshold of 0.2 μm increases bacteria retention [ 29 ]. Therefore, the surface of a restoration is of considerable importance because it affects the function of a tooth through wear, abrasiveness, and build-up of plaque and calculus [ 30 ]. A smoother restoration has a better wear resistance and marginal integrity thus increasing the life of the restoration and the oral health of the patient [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies concluded that toothbrushing significantly increases surface roughness [ 24 , 27 ] and any surface roughness above a threshold of 0.2 μm increases bacteria retention [ 29 ]. Therefore, the surface of a restoration is of considerable importance because it affects the function of a tooth through wear, abrasiveness, and build-up of plaque and calculus [ 30 ]. A smoother restoration has a better wear resistance and marginal integrity thus increasing the life of the restoration and the oral health of the patient [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some differences may exist amongst the RPDs that possibly in uenced the GI scores between the PWA group and the control group. Given that the participants received their RPDs within a 2-year duration, increased surface roughness in old dentures [40] could affect cleanliness.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 This situation occurs principally because of the surface roughness of the acrylic resin, which tends to increase through time due to its low resistance to abrasion and daily brushing with dental pastes containing abrasives. [14][15][16] It is important to emphasize that the accumulation of microbial plaque on the complete denture can lead to bad breath. 12,13 The relining of a complete denture can be done in a direct manner in the clinic, or indirectly, combining the clinical and laboratorial phase.…”
Section: Introductionmentioning
confidence: 99%
“…This is important since complete dentures can accumulate and retain a microbial film over time, 12 13 worsening oral hygiene and affecting the health of patients. 14 15 This situation occurs principally because of the surface roughness of the acrylic resin, which tends to increase through time due to its low resistance to abrasion and daily brushing with dental pastes containing abrasives. 14 15 16 It is important to emphasize that the accumulation of microbial plaque on the complete denture can lead to bad breath.…”
Section: Introductionmentioning
confidence: 99%